Attribution of human characteristics and bullying involvement in childhood: Distinguishing between targets. Issue 4 (16th November 2015) - van Noorden, Tirza H. J.; Haselager, Gerbert J. T.; Lansu, Tessa A. M.; Cillessen, Antonius H. N.; Bukowski, William M.
Abstract : This investigation researched the association between the attribution of human characteristics and bullying involvement in children by distinguishing between targets. Study 1 focused on the attribution of human characteristics by bullies, victims, bully/victims, and non‐involved children toward friends and non‐friends. The data from 405 children ( M = 10.7 years old) showed that they attributed fewer prosocial and more antisocial human characteristics to non‐friends than to friends. Moreover, boy victims attributed fewer prosocial human characteristics to non‐friends than boy bullies and non‐involved boys did. In addition, victims attributed more antisocial human characteristics to non‐friends than non‐involved children did. Study 2 addressed bullies', victims', bully/victims', and non‐involved children's attribution of human characteristics to each other. The data of 264 children ( M = 10.0 years old) showed that bullies, victims, and bully/victims attributed fewer prosocial and more antisocial human characteristics to each other than to non‐involved children. Non‐involved children attributed fewer prosocial human characteristics to bully/victims than to bullies and victims, and more antisocial human characteristics to bully/victims than to victims. In addition, girls attributed more prosocial and fewer antisocial human characteristics to girls than to boys, whereas boys did not distinguish between girls and boys. Based on these findings, suggestions for future research are provided and implications for bullying prevention and intervention are discussed. Aggr. Behav. 42:394–403, 2016. © 2015 Wiley Periodicals, Inc.